Decolourisation of reactive black 5 by Klebsiella Pneumoniae isolated from Antarctica seawater - Ameerah Tharek, 1991-, author 639131 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Sarjana Sains (Bioteknologi)) - Universiti Teknologi Malaysia, 2016